Integrating opportunistic glaucoma screening into general health examinations in China: A pilot study. (20th June 2019) - Zhang, Shaodan; Sun, Jing; Liu, Shanshan; Liang, Yuanbo; Hu, Ying; Congdon, Nathan; Pang, Chi Pui; Wang, Hailin
Abstract: Importance: Under‐detection and late diagnosis are major causes of glaucoma‐related visual impairment. Cost‐effective opportunistic glaucoma screening is of great interest in the early identification and prevention of glaucoma. Background: To describe the results of a health examination centre‐based opportunistic glaucoma screening and referral model. Design: This single centre cross‐sectional study was conducted in a health examination centre affiliated to a tertiary hospital in Shenyang, northeastern China. Participants: From 21 March to 30 September 2016, 14 367 individuals aged ≥ 30 years undergoing routine physical examinations were invited for this glaucoma screening. Methods: Presenting visual acuity, non‐contact pneumotonometry and non‐mydriatic fundus photography were evaluated. Fundus photographs were classified as non‐glaucoma, possible, probable and definitive glaucoma. Participants with probable and definite glaucomatous discs or intraocular pressure ≥ 24 mmHg were referred for definitive examinations. Main Outcome Measures: Detection rate of glaucoma suspects and ocular hypertension (OHT). Cost to identify a single case with suspected and diagnosed glaucoma was also calculated. Results: Altogether, 277 glaucoma suspects and 327 ocular hypertension suspects were identified. Among 190 participants with probable/definite glaucomatous discs, 93 (48.9%) accepted further examination. Among these, 78 were diagnosed as glaucoma, seven as suspects and eight were excluded. Only 98 ocular hypertension suspects (30.0%) accepted further examinations: eight had primary angle closure and 23 had confirmed ocular hypertension. The cost to identify a single glaucoma suspect and definite glaucoma case were US$135 and US$857, respectively. Conclusions and Relevance: This novel screening model provides opportunities to improve glaucoma detection at low cost. Interventions to improve follow‐up are needed.